Morphogenetic reaction in tissue culture of leguminous plants (Experimental biology, 2015)
Brief overview of modern data on the morphogeny of leguminous plants in vitro conditions is presented. Considerable progress is shown for studies on morphogenic potential in tissue culture of leguminous plants.
Keywords: plants tissue culture; morphogenesis; legumes